Electromagnetic Brain Imaging A Bayesian Perspective - Sekihara, Kensuke; Nagarajan, Srikantan S. (Springer International Publishing : Imprint: Springer, 2015)
This graduate level textbook provides a coherent introduction to the body of main-stream algorithms used in electromagnetic brain imaging, with specific emphasis on novel Bayesian algorithms.  It helps readers to more easily understand literature in biomedical engineering and related fields, and be ready to pursue research in either the engineering or the neuroscientific aspects of electromagnetic brain imaging.  This textbook will not only appeal to graduate students but all scientists and engineers engaged in research on electromagnetic brain imaging.